Jurnal Vokasi IMPLEMENTASI PRINSIP 5A PADA STRATEGI PENINGKATAN JUMLAH KUNJUNGAN WISATAWAN PASCA PANDEMIC CORONAVIRUS DESEASE (COVID-19): STUDI KASUS DI TWA. GUNUNG TANGKUBAN PERAHU: Usaha Perjalanan Wisata - Laela Susanto; Anggi Permata Karismatika (Politeknik Bisnis Mayasari, 2022)
The recovery of a tourist area cannot be separated from the role of stakeholders in it, both from the government, the private sector, and the community. A tourist area does not just exist without the parties who go directly and focus on managing the tourist area so that it can continue to run and develop. The good development of a tourist area can be marked by a recovery strategy after the Coronavirus disease 19 (Covid-19) pandemic with an increase in numbers both in the number of visitors, income, and others. As in the Tangkuban Perahu Natural Park, the management needs to carry out a recovery strategy that can contribute to the fulfillment of the 5A component in tourism so as to increase the number of tourist visits. The data obtained came from the results of interviews and direct observations to the research site and literature review concerned with the object of study through library research, namely literature and information media related to the discussion. So it was found that the tourism component of Tangkuban Perahu Natural Park was complete. Development strategy. Tangkuban Perahu Natural Park is to provide a sense of security and comfort with adequate health protocols. Apart from that currently Tangkuban Perahu Natural Park has a new spot, namely as a means that tourists can use to capture their visit at no additional cost. The strategy carried out by the company. Tangkuban Perahu Natural Park is already good, but it will be even better if the company can maintain the cleanliness of the existing facilities, collaborating with the media to promote tourist attractions. The implementation of this strategy is expected to be optimal if each stakeholder has a balanced role in their respective fields so that they can collaborate well and produce good strengths.